Assessment of validity and reliability of Malay version of asthma control test questionnaire - Mustaffa Kamal, Shahiniz Tasneem (2015)
OBJECTIVE To validate the Malay version of ACT questionnaire for asthma children aged 12 to 18 years old . METHODS Pilot test was administered as linguistic validation before proceeding with data collection. The participants completed the ACT questionnaire concurrently while performing the spirometry. Respiratory paediatricians who were blinded to ACT rated their asthma control based on Global Initiative for Asthma (GINA) guideline in order to evaluate validity and reliable of Malay version of ACT. RESULTS A total of 60 patients were recruited with median age of 14 years old. The Malay version of ACT has good internal consistency; Cronbach’s alpha 0.91. A significant difference was noted between the different groups of asthma control control as grouped by the GINA - defined classification [F(2,25) =88.16. There was good agreement of ACT with the specialist classification, kappa = 0.84. The study has good sensitivity and specificity for cut off 19 with 92% and 96% respectively. It has fair correlation with FEV1 and PEF (r = 0.41-0.42). CONCLUSION The Malay version of ACT is a valid and reliable test for asthma control assessment . Further research for validation needed involving multi centre, bigger sample size and repeated measures to detect the changes over time in order to capture the true picture of asthma control, are required to validate the result of this study.